The Influence of Greenpeace Advocacy Towards CIMB International on the Issue of Coal Power Plant Financing Discharge in Indonesia - Shafar, Wildan Ilmanuarif; Isnaeni, Nurul (Global Strategis, 2022)
In 2020, Greenpeace and several Indonesian NGOs formed a Transnational Advocacy Network (TAN) called The Hotter Earth Coalition to influence Bank CIMB's funding policy. In the period 2010-2020, CIMB is one of the financial institutions with the largest total investment in the coal sector in Southeast Asia, including in Indonesia. This advocacy then got its result when CIMB announced that they would stop financing coal starting in 2021. This article aims to explain the influence of Greenpeace's TAN advocacy on the CIMB's policy change. Using the concept of advocacy strategy by Keck & Sikkink and the level of influence of advocacy by Daniel McCormick, the results of this study conclude that the advocacy strategy carried out by TAN Greenpeace has succeeded in influencing CIMB's policy changes. This article finds that even though advocacy is carried out from outside the decision-making process of the targeted actor, NGOs can still exert influence mainly through information & accountability politics. Keywords: Transnational advocacy network, NGOs influence,  Greenpeace, environmental issues. Pada tahun 2020, Greenpeace dan beberapa NGOs Indonesia membentuk Transnational Advocacy Network (TAN) bernama The Hotter Earth Coalition untuk mempengaruhi kebijakan pendanaan Bank CIMB. Dalam kurun waktu 2010-2020, CIMB merupakan salah satu institusi keuangan dengan total investasi terbesar pada sektor batubara di Asia Tenggara. Pada Desember 2020, advokasi yang dilakukan oleh koalisi Greenpeace tersebut kemudian membuahkan hasil ketika CIMB mengumumkan bahwa akan menghentikan pendanaan batubara mulai tahun 2021. Artikel ini bertujuan menjelaskan pengaruh advokasi TAN Greenpeace terhadap perubahan kebijakan tersebut menggunakan konsep strategi advokasi oleh Keck & Sikkink dan tingkat pengaruh advokasi oleh Daniel McCormick. Hasil dari penelitian ini menyimpulkan bahwa strategi advokasi yang dilakukan TAN Greenpeace berhasil mempengaruhi perubahan kebijakan CIMB. Artikel ini menemukan bahwa meskipun sebuah advokasi dilakukan di luar proses pengambilan keputusan aktor yang ingin dipengaruhi, NGOs tetap dapat memberikan pengaruh terutama melalui penerapan strategi advokasi politik informasi dan akuntabilitas. Kata kunci: Jaringan advokasi transnasional, pengaruh NGO, Greenpeace, isu lingkungan.